Postdisaster Reconstruction After the 2021 Floods From the Neighborhood Perspective - Marisa Fuchs (Journal of Flood Risk Management, 2025)
ABSTRACT The floods in Western Europe in July 2021 demonstrated the diverse ways and varying paces at which neighborhoods recover from disasters. Based on two exemplary neighborhoods affected by the floods in the city of Hagen, Germany, this study examines the reconstruction process, highlighting the influence of social vulnerabilities and community resilience on private reconstruction processes. Despite differing contexts, both case studies demonstrated a significant reliance on external support during reconstruction. Individual needs varied based on social vulnerabilities within and between population groups, primarily manifesting as challenges in information dissemination and access to support services like funding and expertise. The findings reveal differences in the ability and capacity of neighborhoods to collectively address these vulnerabilities. While small neighborhood networks effectively facilitated information sharing in both cases, one case study relied more heavily on external assistance from nonprofit organizations for larger and longer‐term community‐driven initiatives. The study underscores the need for improvements in postdisaster reconstruction governance. Public authorities predominantly view neighborhoods as recipients rather than partners in the reconstruction process, without adequately addressing their social vulnerabilities within their governance approaches. Supporting local social infrastructures is crucial, as they connect formal reconstruction with the neighborhood, aiding resource access and resilience building.